Electrotechnological Heat Treatment of Milk: Energy and Exergy Efficiency - Andrei A. Bagaev; Sergey O. Bobrovskiy (Техника и технология пищевых производств)
The dairy industry needs new and more energy-efficient technological procedure for milk pasteurization. This article introduces a comparative efficiency assessment of various milk pasteurization technologies and electrotechnological means. The study featured milk, which was heated from 20 to 75°C with a capacity of 1000 kg/h at an estimated power of 58.95 kW. The treatment involved a steam-to-milk pasteurizer with electric indirect or direct heating, an induction pasteurizer, and a thermosiphon pasteurizer with direct or indirect electric heating. The study relied on the methods of energy and exergy analyses. The system of steam-to-milk pasteurizer with electric indirect (elemental, induction) or direct (electrode) heating demonstrated the following indicators: exergy loss – 1.29 kW, power consumption – 71.29 kW, exergy efficiency – 0.99, energy efficiency – 0.827. The thermosiphon pasteurizer with direct or indirect electric heating demonstrated the following properties: exergy loss – 1.29 kW, power consumption – 60.92 kW, exergy efficiency – 0.99, energy efficiency – 0.9676. The induction pasteurizer had the least competitive parameters: exergy loss – 10.8 kW, power consumption – 70.43 kW, exergy efficiency – 0.867, energy efficiency – 0.837. The thermosiphon pasteurizer with direct or indirect electric heating was able to increase the energy efficiency of milk pasteurization, while the induction pasteurizer proved to be a promising R&D direction.